2016
DOI: 10.1007/s11746-015-2781-6
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Profile and Chemical Composition of Egyptian Moringa oleifera Seed Oils

Abstract: Moringa oleifera is grown all over the world as a crop for its nutritious pods, leaves and seeds. The purpose of the present study was to evaluate the oil percentage, density, iodine value, saponification value, acid value and fatty acid profile of Egyptian moringa Seed oils. Moringa seeds were irradiated using 60Co at dose levels of 0.0 (control), 5, 10 and 15 kGy and oil was extracted from unirradiated and irradiated samples. Results showed that the oil percentage and density were almost unaffected. Irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
5
16
0
Order By: Relevance
“…It is noteworthy that both oils possess very low AV and PV, suggesting their good quality as edible oil. These results are in agreement with (Aly et al, ) those obtained for Egypt . Either iodine value or unsaponifiable matter content of the aqueous enzymatic extracted oil was a little higher than that of the Soxhlet extracted oil ( P < 0.05).…”
Section: Resultssupporting
confidence: 94%
“…It is noteworthy that both oils possess very low AV and PV, suggesting their good quality as edible oil. These results are in agreement with (Aly et al, ) those obtained for Egypt . Either iodine value or unsaponifiable matter content of the aqueous enzymatic extracted oil was a little higher than that of the Soxhlet extracted oil ( P < 0.05).…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, Naresh, Varakumar, Variyar, Sharma, & Sarathi Reddy (2015) indicated that the degradation of conjugated phenolic compounds should define the higher phenolic content in gamma-irradiated date samples. In the same concern Aly, Maraei, & Ali (2016) found that phenolic and flavonoids were significantly expanded by expanding irradiation dose levels of Egyptian Moringa oleifera seed oils. On the other side, Carocho et al (2012) demonstrated that contents of flavonoid decreased in chestnut Table 3.…”
Section: Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 85%
“…Several studies have shown that palm dates include flavonoids such as quercetin, luteolin, and apigenin, as well as phenolics such as ferulic, sinapic, p-coumaric acids, and derivatives of cinnamic acid (Sanchez-Moreno, 2002). The radical DPPH in oil produced by unirradiated and irradiated Moringa oleifera seed oil showed that scavenging activity gradually increased by increasing the amount of irradiation dose to 10 kGy (Aly, Maraei, & Ali 2016).…”
Section: Antioxidant Activity Using Dpph Radicalmentioning
confidence: 99%
“…Moringa oleifera (M. oleifera L.) has been called the "Miracle Tree" because every part of the tree including leaves, oilseed, stem, and roots has a beneficial properties in nutrition or in pharmaceutical purposes (Gopalakrishnan et al, 2016;Aly et al, 2016;Azad et al, 2015). It belongs to the family of Moringaceae, and it is widely cultivated across the world.…”
Section: Moringa Oilseedmentioning
confidence: 99%
“…Moringa oil is rich in palmitic, stearic, behenic, and oleic acids. Oleic unsaturated omega-9-fatty acid is about 76.29%, and saturated acids were palmitic, stearic acid, and arachidic up to 12.66% (Aly et al, 2016). The seeds of Moringa oleifera are used in water treatment as natural coagulant.…”
Section: Moringa Oilseedmentioning
confidence: 99%